Risk Factors for Patients with Gonococcal Urethritis at Dr. Hasan Sadikin General Hospital Bandung, Indonesia in 2013–2019 - Pati Aji Achdiat; Jefferson Basta Erguna Ginting; Chrysanti Chrysanti (Althea Medical Journal, 2023)
Background: Gonorrhea is the second most common sexually transmitted infection in Southeast Asia. Many factors cause gonococcal urethritis, and each region has its characteristics. This study aimed to determine the risk factors among patients with gonococcal urethritis at Dr. Hasan Sadikin General Hospital Bandung. Methods: This was a descriptive study with a retrospective and total sampling method, reviewing the gonococcal urethritis patient medical records obtained from Dr. Hasan Sadikin General Hospital Bandung from 2013 to 2019. Sociodemographic, clinical manifestations, and sexual or risky behaviors data were collected.Results: Among 97 males with gonococcal urethritis, unmarried males (54.6%) and the age category of 20–24 years (35.1%) were predominant, with high school education/equivalent (58.8%). Based on their sexual behavior, the majority had more than one sexual partner in the past month (63.9%) and had never used a condom when having sex (55.7%). Additionally, there was also a group of man who had sex with man (MSM) (14.4%) and illicit drug users (19.5%).Conclusions: Males in the young adult age group, single, have a high education level, have multiple sexual partners, and never used a condom during having sex, have a higher risk of having gonococcal urethritis. Identifying these most reported risk factors may help health care providers design effective prevention strategies. Unmarried young adults should be a primary focus in receiving educational programs. They should be informed regarding the impact of multiple sexual partners, condom usage, and illicit drug on gonococcal urethritis infection among men.